Harnessing beneficial bacteria to remediate antibiotic-polluted agricultural soils: integrating source diversity, bioavailability modulators, and ecological impacts - Olanrewaju, Oluwaseyi Samuel; Bezuidenhout, Cornelius Carlos (Frontiers in Microbiology, 2025)
Antibiotic contamination in agricultural soils, primarily from manure application and wastewater irrigation, has emerged as a critical threat to food security, environmental health, and public safety due to the proliferation and persistence of antibiotic-resistant genes. This review examines the diverse sources and ecological impacts of antibiotics in soil, including their alteration of microbial community structures, promotion of horizontal gene transfer, and subsequent risks to plant and human health. It further evaluates how soil properties, such as pH, organic matter content, and texture, influence the bioavailability of antibiotics and modulate their degradation dynamics. Emphasis is placed on the bioremediation potential of beneficial bacteria, detailing key mechanisms such as enzymatic biodegradation, biosorption, biofilm formation, and the formation of synergistic microbial consortia capable of utilizing antibiotics as nutrient sources. In addition, the manuscript critically discusses the regulatory, technological, and scalability challenges inherent to deploying microbial bioremediation strategies, including integrating gene editing and systems biology approaches under a One Health framework. By synthesizing molecular insights with environmental and policy considerations, this review provides a comprehensive assessment of current bioremediation strategies and outlines future directions to mitigate the ecological and health risks associated with antibiotic pollution in agricultural ecosystems.